Greek History. (25th March 2015) - Unknown
Abstract : This review commences with two important recent books on archaic Greek history. Hans van Wees sees fiscality as a main aspect of the development of Greek communities in the archaic period. He explores the trajectory of Greek, and more specifically Athenian, fiscality in the course of the archaic period from personal to institutional power, from informal to formal procedures, and from undifferentiated to specialized offices and activities. Van Wees argues convincingly that navies based on publicly built and funded triremes appeared from 530s onwards as a Greek reaction to the emergence of the Persian Empire; the resources for maintaining such navies revolutionized Greek fiscality. This means that the Athenian navy emerged decades before its traditional attribution to the Themistoclean programme of the 480s; but this revolution would have been impossible without the gradual transformation of Athenian fiscality in the previous decades from Solon onwards, as regards the delimitation of institutional and specialized fiscal offices, such as the naukraroi and kolakretai, and the creation of formal procedures of taxation like the eisphora . This is a very important book that should have significant repercussions on the wider study of archaic Greece and Athenian history; but it also raises the major issue of the nature of our written sources for archaic Athens. While van Wees's use of the sources is plausible, there does not seem to be any wider principle of selection than what suits the argument (very sceptical on the tradition about Solon's fiscal measures, or Themistocles' mines and navy policy; accepting of traditions about Hippias' and Cleisthenes' fiscal measures). We urgently need a focused methodological discussion of the full range of sources and the ways in which tradition, anachronism, ideology, and debate have shaped what we actually have.